Propuesta de implementación de un sistema de gestión de seguridad y salud en el trabajo (sgsst) para disminuir el índice de accidentabilidad en el sector de redes y telecomunicaciones en lari contratistas s.a.c. - Castillo Saenz, Evelin Melissa (2017)
The present research study called "IMPLEMENTATION PROPOSAL OF A SECURITY AND HEALTH MANAGEMENT SYSTEM AT WORK (SHMSW) TO REDUCE THE ACCIDENTABILITY INDEX IN THE NETWORK AND TELECOMMUNICATIONS SECTOR IN LARI CONTRATISTAS S.A.C", seeks to achieve the objective to reduce the accidentability index of the supply process in the company Lari Contratistas in the branch office of Trujillo in the sector of networks and telecommunications, in which a great accidents number was registered and that they are more exposed to high risk hazards in their work environment. The method used before the SGSST proposal showed that the monthly average accidentability index is 0.47 in 2016, which will be reduced because this factor would represent a high number of accidents and/or a large number of lost days (days not worked), affecting the direct and indirect costs in a negative way for the company. In order to reduce the accidentability index, the OHSAS 18001: 2007 methodology was used in the SGSST proposal, which is compatible with the current legislation in our country that allowed us to plan to identify, evaluate and control risks, identify documentation needs management system, in addition to measuring, supervising and improving the performance of the OSHMS, concluding that by 2017 with the of SHMSW proposal would decrease the accidentability is index equal 57% less with respect to the previous year. It is an important factor the leadership of the top management in the SGSST so that it is possible to promote a prevention culture of the system and a continuous improvement of it.